Carbohydrate antigen 19‐9 is a useful prognostic marker in esophagogastric junction adenocarcinoma. (26th August 2015) - Tokunaga, Ryuma; Imamura, Yu; Nakamura, Kenichi; Uchihara, Tomoyuki; Ishimoto, Takatsugu; Nakagawa, Shigeki; Iwatsuki, Masaaki; Baba, Yoshifumi; Sakamoto, Yasuo; Miyamoto, Yuji; Yoshida, Naoya; Oyama, Shinichiro; et al.
Abstract : Preoperative serum carbohydrate antigen 19‐9, which was significantly correlated with depth of tumor invasion, is a useful prognostic marker in patients with esophagogastric junction adenocarcinoma. Abstract: The incidence rate of esophagogastric junction (EGJ) adenocarcinoma has been rapidly increasing worldwide. Carcinoembryonic antigen (CEA) and carbohydrate antigen 19‐9 (CA19‐9) are major serum tumor markers in gastrointestinal cancers. However, the role of these markers in EGJ adenocarcinoma has not been thoroughly investigated. A total of 211 patients with EGJ adenocarcinoma who underwent surgery or endoscopic submucosal dissection at two academic institutions, Kumamoto University Hospital or Kyushu University Hospital between January 1996 and March 2014, were eligible for this study. Serum CEA and CA19‐9 were examined within 1 month before resection. The cut‐off values for CEA and CA19‐9 were set at 5.0 ng/mL and 37 U/mL, respectively. The clinicopathological features and prognostic roles of the markers were examined using univariate and multivariate analyses. The positive ratios for preoperative CEA (>5.0 ng/mL) and CA19‐9 (>37 U/mL) were 20.3% and 12.9%, respectively. The positive ratio of CEA and CA19‐9 was significantly higher in patients with tumors invading muscular or deeper layers ( P  =   0.002 and <0.001, respectively). Cox proportional hazards model revealed that CA19‐9 positivity, but not CEA positivity, was an independent prognostic factor in patients with EGJ adenocarcinoma for cancer‐specific survival (multivariate hazard ratio [HR] = 3.89, 95% confidence interval [CI] 1.41–10.33; P =  0.010) and overall survival (multivariate HR = 2.43, 95% CI 1.03–5.35; P =  0.043). Preoperative serum CA19‐9 is a useful prognostic marker in patients with EGJ adenocarcinoma.